Решение задания 15, вариант 15, Ященко 36 вариантов, ЕГЭ-2017

вариант 15 задание 15
ln(2x^2+x-1)/(11x-6-3x^2)  /  ln (3x-1)/(x+2) >=0
{ (2x^2+x-1/11x-6-3x^2)  -1 }  * {(3x-1/x+2) -1} >=0

2x^2+x-1 > 0  , ( -\infty , -1) U ( 1/2, + \infty)
11x-6-3x^2 >0  , (2/3 ,  3)
x<>-2
x<>1/3 ,  1.5
(3x-1)/(x+2) > 0 ,  (-\infty, -2) U ( 1/3, + \infty)
(3x-1)/(x+2) <> 1

ОДЗ (2/3, 1.5) U(1.5, 3)
( (2x^2+x-1)/(11x-6-3x^2)  -1 )  * ((3x-1)/(x+2) -1) >=0

(2x^2+x-1)/(11x-6-3x^2)  -1 =   (2x^2+x-1) - (11x-6-3x^2) / (11x-6-3x^2) =( (5 * x^(2)) - (10 * x) + 5 ) /   (11x-6-3x^2) = 5(x-1)^2 / (x-3)(x-2/3) (-)
{(3x-1)/(x+2) -1} =( 3x-1 ) - (x+2) / (x+2) = (2x-3) / (x+2)

5(x-1)^2 / (x-3)(x-2/3) (-)   * (2x-3) / (x+2) >=0

— -2 + ⅔ — 1 — 3/2 + 3 —
Ответ (1) U  (1.5, 3)

{ ln (2x^2+x-1) - ln (11x-6-3x^2)  } /  ln ((3x-1)/(x+2))  >=0
{ ln (2x^2+x-1) / (11x-6-3x^2)  } /  ln ((3x-1)/(x+2))  >=0

{  (2x^2+x-1) / (11x-6-3x^2) -1 }  * { (3x-1)/(x+2)  -1 } >=0
(2x^2+x-1) >0
(11x-6-3x^2)>0
(3x-1)/(x+2)>0
(3x-1)/(x+2)<>1

{  (2x^2+x-1) / (11x-6-3x^2) -1 } = { (2x^2+x-1) -  (11x-6-3x^2)  }  /  (11x-6-3x^2) =  (5 * x^(2)) - (10 * x) + 5  /  (11x-6-3x^2) = 5 (x-1)^2 / -(x-3)(3x-2)

11x-6-3x^2 = -3x^2 +11x-6= -3(x-3)(x-2/3)=-(x-3)(3x-2) 3 и 2/3

(3x-1)/(x+2)  -1 = { 3x-1 - (x+2) } / (x+2) = (2 * x) - 3 / (x+2)

5 (x-1)^2 / -(x-3)(3x-2)  * (2x-3)/(x+2) =  5 (x-1)^2 *  (2x-3) /  -(x-3)(3x-2)*(x+2)

— -2 + ⅔ — 1, — 1.5 + 3 —

(2x^2+x-1)  >0      ( -\infty, -1)     U  (½  , +\infty)
(11x-6-3x^2)>0     (⅔ , 3)
(3x-1)/(x+2)>0      -\infty,-2)  U ( ⅓ , +\infty)
(3x-1)/(x+2)<>1
3x-1 - (x+2) <>0  2x-3<>0   x<>1.5     x<>-2
(\frac{2}{3} , 3)без точки 1.5
{1}U(1.5,3)

Добавить комментарий

Ваш e-mail не будет опубликован.